Design of an integrated library system with metadata schema creation and selection through entity relationship modeling of selected special libraries in Metro Manila - Santillan, Sara Gabriella L.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
The field of information science continues to expand, and as such new fields of inquiry must be answered in conjunction with methods imbibed by the field through its interdisciplinary nature. The study of library automation has received some attention in the past, but never in conjunction with the recent developments in metadata standards or with the intent to design integrated library systems (ILSs). The research focused on special libraries in Metro Manila to see if their particular institutions had different data fields other than the AACR2R standard and/or had special vocabularies for their field of specialization, and what data was recorded for their processes. The data gathered served as a basis for creating the design of the ILS.
The researcher interviewed (5) librarians in the following institutions: SEAMEO INNOTECH, the Occupational Health and Safety Center, Goethe-Institut, the Lopez Memorial Museum and Library, and the House of Representatives. Document analysis was also performed on forms (softcopy and hardcopy) and where hardcopy samples could be obtained, they were. Based on this data, the researcher applied entity-relationship modeling and principles of database design to create a database which incorporated most of the processes and data which the institutions used. For bibliographic description, four (4) metadata standards were selected based on what closely adhered to the needs of the libraries. From there the user can select what kind of metadata is kept about a record. The following standards were selected: Metadata Object Description Schema (MODS), Simple Dublin Core (SDC or DC), a mix of cataloging Cultural Objects (CCO) and Categories for the Description of Works of Art (CDWA) and an application of Dublin Core called the Dublin Core Education Application Profile (DC-ED).
The data gathered revealed that special libraries often apply standard AACR2R rules but that subject headings and classification rules are often more limited and specialized, Particularly in the Lopez Memorial Museum and Library, the librarians created terms and corresponding cutter number for geographic places as the Dewey Decimal System did not cover all the places in the Philippines. The libraries showed much regularity in the data tracked for acquisitions and circulation. In preservation, only the Lopez Museum and Library had a comprehensive system for recording preservation activity, while the House of Representatives library outsourced preservation activity and kept documentation in the form of reports.
The database design presented here can be developed into a full software as it includes an analysis of the functions and modules distribution that an ILS should have. In the area of pure research the findings here show that special libraries in a particular field may wish to create standards for vocabularies beyond what is given in the rules which are often imported from abroad. The findings here also indicate that the libraries are moving towards being more streamlined and paperless, and the findings here can also be used to design other special databases.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Integrated library systems (computer systems).; Special libraries -- Philippines -- Quezon City; Special libraries -- Philippines -- Makati City; Special libraries -- Philippines -- Pasig City